ادارة البيانات المفتوحة وتفعيلها عبر مواقع الجامعات الحکومية السعودية - غيداء عبد الحفيظ شقدار (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to know the current status of open data platforms in Saudigovernment’s universities and to analyze them according to standardized criteria.The comparison between them have done to know the extent of activation ofopen data and the similarities and differences among them. Therefore, thecontribution of this study is to develop them and provide the best model ofplatform open data among Saudi universities. The survey methodology was usedto survey 29 public universities in Saudi Arabia to know their effectiveness inopen data management.Furthermore, the analytical descriptive approach was used to describeand analyze open data platforms in Saudi government’s universities and thecomparative approach was used to compare them through the checklist anddirect observation. One of the most important results of this study is theavailability of open data platforms across 21 Saudi government’s universities.However, most of them achieve less than the average of the standard criteria ofevaluating the open data platforms.Six government’s universities in Saudi Arabia achieved intermediatepercentages in their open data platforms. These universities are the SaudiElectronic University, Tabuk University, King Abdulaziz University, King FaisalUniversity, Majma'a University, and Imam Abdul Rahman Bin Faisal University.The open data platform at Prince Sattam bin Abdul Aziz University has the firstrank where it achieved the highest percentage of 66.7%.  The open data platforms at King Saud University and Najran Universityachieved 60.6%. However, al Baha open data platform received the lowestpercentage of 18.2%. In conclusion, open data portals in all Saudi publicuniversities have not achieved the completeness percentage and they shouldhave development. Consequently, the most important recommendations of thestudy are open data should be available in all sites of the Saudi governmentuniversities. In addition, all portals and open data platforms should havedevelopment to achieve the high percentage of completeness. Finally, increasethe awareness of open data and its importance through the open data platformsin the Saudi public universities